The Little Data Book on Financial Development 2014 - World Bank. (Washington, D.C. The World Bank, 2014)
The Little Data Book on Financial Development 2014 is a pocket edition of the Global Financial Development Database, published as part of the work on the Global Financial Development Report 2014: Financial Inclusion. It contains 38 indicators of financial development in 205 economies, including measures of (1) financial depth, (2) access, (3) efficiency, and (4) stability of financial institutions and markets. Additional variables, historical observations, and links to underlying research are available at www.worldbank.org/financialdevelopment.
Electronic reproduction.
Keywords: Finance -- Statistics; Finance -- Government policy -- Statistics; Financial institutions -- State supervision -- Statistics; International finance -- Statistics; Electronic books